Sporty Design on the Body of the Honda Civic Gen 10 - Wafa Ulin Nuha; Ahadiat Joedawinata (ARTic, 2021)
The Honda Civic car is a sedan that adheres to a front-wheel drive system which was launched in 1972. Over time, Honda's design The Civic has undergone many changes, until now the Honda Civic has entered its tenth generation which was launched in 2016. The 10th gen Honda Civic car has a sporty this is based on a futuristic body shape. This research was conducted to review the design form of the Honda Civic gen 10 by identifying the elements visual that represents Sporty design. This study uses a qualitative method descriptive, the purpose of this descriptive research is to make a systematic, factual and accurate description, picture, or analysis of the facts, characteristics and relationships between the phenomena studied. Keywords: Design, Honda Civic, Sporty